KEMAMPUAN PELAPUKAN 10 STRAIN JAMUR PADA LIMA JENIS KAYU ASAL KALIMANTAN TIMUR - Djarwanto; Sihati Suprapti (BRIN Publishing, 2014)
Five wood species from Dipterocarpaceae have been exposed to ten fungus strains, then were evaluated using SNI 7207:2014. The results shows that the most capable fungi to decay wood from the highest to the lowest are Schizophyllum commune (white rot fungi), Trametes sp., Pycnoporus sanguineus, Tyromyces palustris, Phlebia brevispora, Polyporus sp. HHB1-209, Polyporus sp. HHB1-371, Chaetomium globosum, Dacryopinax spathularia, and Lentinus lepideus (brown rot fungi). The highest weight loss was occured on Dipterocarpus glabrifgemmatus wood by S. commune. While the lowest weight loss was on Dipterocarpus glabrifgemmatus and Shorea hopeifolia wood by L. lepideus. The fifth of wood i.e. keruing (Dipterocarpus pachyphyllus, D. stellatus, D. glabrifgemmatus), meranti (Shorea hopeifolia) and resak (Vatica nitens) are belong into resistant wood (class II).